(untitled) (Bangladesh Journal of Pharmacology, 2012)
Pure cultures of Trichoderma harzianum, T. aureoviride, T. reesei, T. koningii and T. hemantum were checked for their potential to produce cyclosporin A. Production medium used for drug production was consisted of: glucose, 5%; peptone, 1%; KH2PO4, 0.5%; KCL, 0.25% (w/v). Whereas, butyl acetate was used to extract the fermentation medium for cyclosporine A. This was then analyzed through High Performance Liquid Chromatography and the chromatograms obtained were compared with that of cyclosporine and with the external standard cyclosporin A 98.5% pure. Only chromatogram of T. harzianum showed a peak at 2.779, which was comparable with both the standards. Mass spectroscopy of this peak showed [CsA + H] + ion of m/z 1203. The amount of drug calculated was 44.06 µg/mL.